The effect of continuous nitrate intake on the disease prognosis in patients with vasospastic angina pectoris according to prolonged outpatient monitoring - A. S. Ryazanov; K. I. Kapitonov; M. V. Makarovskaya; A. A. Kudryavtsev (Кардиоваскулярная терапия и профилактика, 2019)
Aim. Although nitrates are widely used as a concomitant therapy with calcium channel blockers (CCBs) for vasospastic angina (VSA), their prognostic contribution remains unclear. The present study aimed to examine the prognostic impact of chronic nitrate therapy in patients with VSA.Material and methods. 129 patients with VSA, registrated in clinical diagnostic center, were enrolled in the study (median 66 years, male/ female, 90/39). The primary endpoint was defined as major adverse cardiac events (MACE). The propensity score matching and multivariable Cox proportional hazard model were used to adjust for selection bias for treatment and potential confounding factors. Among the patients, 65 people (49%) were treated with nitrates, including conventional nitrates (for example, nitroglycerin, isosorbide mono- and dinitrate). 36 people received nicorandil. CCBs were used in >90% of patients.Results. During the median follow-up period — 19 months — 21 patients (19%) reached the primary endpoint. Conformity analysis by screening showed that the total incidence of MACE is comparable between patients with and without nitrates (11 vs. 8% at 1 year; risk ratio (RR): 1,28; 95% confidence interval (CI): 0,72-2,28, P=0,40). Although nicorandil has a neutral prognostic effect on VSA (RR: 0,80, 95% CI: 0,28-2,27, P=0,67), the Cox multivariate model has identified potential harm from co-use of conventional nitrates and nicorandil (RR: 2,14, 95% CI: 1,02-4,47, P=0,044), especially with simultaneous treatment with nitroglycerin and nicorandil.Conclusion. Permanent nitrate therapy in combination with CCBs did not improve long-term prognosis in patients with VSA. The additional use of nicorandil has a neutral prognostic effect.